New Model of Islamic Civic EducatÄ±on between Values, Beliefs, Culture and Behavioral Norms Based on Islamic Boarding Schools - Hairus Hairus; Khrisna Hadiwinata; Sri Hudriani (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
The increasing acts of intolerance and the low level of nationalism among teenagers have triggered Madrasah diniyah Miftahul Huda Malang to strengthen values, beliefs, and culture in the learning process to foster the spirit of love for the homeland of the students. This study aims to describe the internalization model of learning by Madrasah Diniyah Miftahul Huda Malang to strengthen values, beliefs, and culture in fostering the spirit of love for the student's homeland. This research is field research. Analysis of the results of interviews, observation, and documentation with the reduction stages, display, and verification. The research analysis results concluded that civic education, which was applied through teaching activities at the Miftahul Huda Islamic boarding school in Malang, was carried out through 1) the value of compliance with the rules and activities while at the Islamic boarding school. 2) the culture of gotong royong cleans up the environment around the pesantren. 3) creative culture through the media of making magazines a forum for students to express their talents and works. 4) gathering activities with the head of the pesantren, teachers, and students.